(untitled) (Research, Society and Development, 2022)
Malaria, still a public health problem in most tropical countries, is caused by protozoa of the genus Plasmodium, three of which are the most common and transmitted by the Anopheles mosquito. Sickle cell anemia is a disease caused by a point mutation that allows the formation of the protein hemoglobin S. Affected individuals are homozygous and develop sickle red blood cells as a result of the phenotype. The purpose of this comprehensive review was to conduct research to demonstrate the relationship between malaria and sickle cell anemia. The review was performed on the regional portal of the VHL and PubMed, with descriptors such as "sickle cell anemia", "malaria" and "Hbs". The association between sickle cell anemia and malaria occurs mainly in malaria-endemic areas. It was therefore concluded that people carrying the sickle cell anemia gene are reluctant to contract malaria.